GLP-1 receptor agonist liraglutide inhibits the proliferation and migration of thyroid cancer cells: Liraglutide inhibits thyroid cancer cells - Zhang, Xuelian; Zhang, Liqiang; Wang, Bo; Zhang, Xuane; Gu, Lei; Guo, Kai; Zhang, Xiaoyan; Zhou, Zunhai (Cellular and Molecular Biology, 2023)
This research was done to find out how liraglutide affected the growth and movement of two human thyroid cancer cell lines overexpressing GLP-1 receptor (migration of medullary thyroid cancer TT/GLP-1R and papillary thyroid carcinoma TCP-1/GLP-1R). Flow cytometer and cAMP assays were used to identify the expression and activation of GLP-1R in two stable cell lines. Counting Kit-8 for Cells was applied to examine the proliferative ability of cells in two stable cell lines after treatment with different concentrations of liraglutide at indicated time points. To track the capacity for cell migration, the Transwell test was utilized. We found that liralutide-activated GLP-1R could significantly reduce the growth and metastasis of two kinds of thyroid tumor cells, and the inhibitory effect was dose- and time- dependent. The phosphorylatios of Akt, S6K1, and 70SK declined after receiving liraglutide therapy In our previous studies, we found that the GLP-1 receptor agonist Liraglutide inhibited the proliferation and migration of thyroid cancer cells through the PI3K/Akt/mTOR pathway. This finding provides a theoretical basis for the treatment of diabetes mellitus complicated with medullary thyroid cancer, and is relatively safe.